A review of archean orogenic gold deposits in greenstone belts and the Slave Province : exploration in the Yellowknife domain, NWT, Canada - Branson, Thomas Keegan (Rhodes University, Faculty of Science, Department of Geology, 2014)
A review of Archean granite-greenstone terranes, orogenic gold deposits, the Slave Province and modern exploration tools, techniques and methods was conducted to identify prospective areas in the Yellowknife domain for hosting orogenic gold deposits and illustrate the best exploration methods for delineating this deposit type. This study identifies Archean granite-greenstone terranes as economically important hosts to quartz-carbonate vein-hosted orogenic gold deposits. These deposits occur at convergent plate margins, but can also be related to local extensional tectonics within a convergent setting. Heat generated from tectonic processes can trigger hydrothermal fluid movement along first-order faults and shear zones. Precipitation of gold-bearing quartz-carbonate veins from the hydrothermal fluids occurs in second- and third-order faults and shear zones related to the first-order structures. This study also identifies the Archean Slave Province in northern Canada as a well-endowed craton with numerous orogenic gold deposits, diamondiferous kimberlites, VMS deposits and several other mineralization styles. In particular, three greenstone belts (Yellowknife, Cameron River and Beaulieu River) associated with likely first-order structures are comprised of prospective rocks for hosting orogenic gold and VMS mineralization. The Yellowknife greenstone belt hosts the past-producing and former world-class Con and Giant orogenic gold deposits, but has been little explored with modern exploration techniques. The Cameron River and Beaulieu River greenstone belts host numerous base and precious metal VMS and BIF-hosted orogenic gold prospects and deposits, indicating mineralization is present. There is considerable potential for significant discoveries to be made using modern exploration techniques in the greenstone belts; however, exploration in the region has been hindered over the past decade by ongoing political negotiations. Once the political negotiations are finalized, application of modern exploration methods and techniques in the prospective greenstone belts should be carried out. Regional scale methodologies should be applied to generate targets using predictive modelling, implicit 3D modelling, 3D geochemistry and exploration targeting so decisions defining a businesses strategy for ground acquisition of high priority targets are made using quantitative analysis. Once ground is acquired, field-based exploration for orogenic gold and VMS deposits should include geological mapping with a focus on structural geology, geochemical sampling and airborne magnetic, radiometric and EM geophysical surveys. Prior to reconnaissance drilling, integration of all data layers and interpretation within a common 3D earth model should be conducted. Following successful reconnaissance drilling, definition drilling along strike and down dip of intersected mineralization, combined with borehole geophysics, should be carried out to delineate the extent of mineralization.
Keywords: Gold ores -- Northwest Territories -- Yellowknife; Gold ores -- Geology; Gold mines and mining -- Northwest Territories -- Yellowknife; Greenstone belts -- Northwest Territories -- Yellowknife; Orogenic belts -- Northwest Territories -- Yellowknife; Prospecting -- Northwest Territories -- Yellowknife; Mining geology; Slave Province (N.W.T. and Nunavut)